Pengaruh Senam Aerobic Terhadap Vo2max Pada Usia 36-45 Tahun Warga Diperumahan Swan Menganti Park Gresik - Utomo, Ari Setyo; Pradita, Angria; Endaryanto, Agung Hadi (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Exercise is an important component of adopting a healthy lifestyle. Inconsistent exercise routines that are limited to holidays are one of the problems that people often face. Methods: This quantitative approach uses a type of experimental research design which aims to see the influence of aerobic exercise on VO2max levels at the age of 36-45 years in the Swan Mengati Park Gresik housing complex. The type of research design used is the one group pre-test and post-test method for conducting research. Initial measurements or pre-test, were carried out before the group was given treatment, and re-measurements or post-test, were carried out at the end of the research session. Results: 30 respondents aged 36-45 years at the Swan Menganti Park Gresik housing complex, that aerobic exercise has a big influence on the level of increase in VO2max. Conclusion: The results obtained were quite significant before doing the exercise with an average graph value of 28,343 to 30,430 after doing the exercise. So, aerobic exercise has a big influence on increasing VO2max which is very important for the healthy function of heart cells, lungs, blood circulation and muscles that work in the body for residents in the Swan Menganti Gresik housing complex. .